Is there correlation between alveolar and systemic bone density? - Paula Cabrini Scheibel; Adilson Luiz Ramos; Lilian Cristina Vessoni Iwaki (Dental Press Editora, 2013)
OBJECTIVE: The present study assessed the correlation between maxillomandibular alveolar bone density and systemic bone mineral density (BMD). METHODS: Dual-energy X-ray absorptiometry of the anterior and posterior maxillomandibular alveolar bone, of the standard sites for the measurement of BMD (lumbar spine and femur) and the third cervical vertebra was performed on 23 middle-aged women. Periapical radiographs were also obtained, with an aluminum step-wedge as reference for the digital reading of apical bone density of the upper incisors. RESULTS: Spearman's correlations coefficients revealed that density in the apical region was correlated with that of the femoral neck (r = 0.433; p < 0.05); BMDs of the posterior regions of the mandible and maxilla were significantly correlated with that of the cervical vertebra (r = 0.554, p < 0.01 and r = 0.423, p < 0.05, respectively); and the anterior maxilla was correlated with the posterior mandible (r = 0.488, p < 0.05). CONCLUSION: Bone density of the maxillary alveolar bone was significantly correlated with that of the femoral neck. Among the bone densities of the alveolar regions, only the anterior maxilla and the posterior mandible were significantly correlated. The findings suggested that bone densitometry might be individually and locally evaluated.